Frequency of Hyponatremia in Chronic Obstructive Pulmonary Disease Patients - Adil Parvez, Waseem Sajjad, Shahzad Gul, Muhammad Mudassar Khan, Babar Riaz (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the frequency of hyponatremia in chronic obstructive pulmonary disease patients. Study Design: Cross-sectional-study Place and duration of study: Medical "A" Unit, MTI Ayub Teaching Hospital Abbottabad from 23rd July 2019 to 22nd January 2020. Methodology: Two hundred and one patients presenting with chronic obstructive pulmonary disease (COPD) were enrolled. Results: One hundred and thirty five (67.2%) patients were male while 66 (32.8%) patients were females. In 30 (14.9%) patients have hyponatremia. Conclusion: Hyponatremia is prevalent in COPD patients, and its frequency was quite higher in patients admitted with COPD. Thus, hyponatremia patient’ should be monitored carefully.